Labor Ideological and Political Education: Promoting the Organic Integration of Labor Education and Ideological and Political Education in Vocational Colleges - Su, Guohui (Transactions on Economics, Business and Management Research, 2024)
The content and purpose of labor education in higher vocational colleges are highly compatible with ideological and political education. It is of great significance to transform labor education based on skill education into labor education based on comprehensive education, integrate labor education into ideological and political education, and promote the ideological and political construction of labor education courses. This article analyzes the shortcomings and shortcomings of labor education in vocational colleges, and proposes to explore the construction of a "labor ideological and political" model for labor education in vocational colleges from three aspects: "for whom to labor", "what labor to do", and "how to labor". Since the release of the Opinions of the Central Committee of the Communist Party of China and the State Council on Comprehensively Strengthening Labor Education in Primary, Secondary, and Large Schools in the New Era, as well as the Guiding Outline for Labor Education in Primary, Secondary, and Large Schools (Trial) issued by the Ministry of Education, labor education has been widely promoted in vocational colleges. More and more educators have realized that labor education is not only a form of employment education and skill education, but also a form of creative education and holistic education, in order to achieve the organic integration of labor education and ideological and political education. It is also an inevitable requirement for vocational colleges to implement the fundamental task of "cultivating morality and nurturing talents" in the new era.